A controlled cost and outcomes analysis of acellular dermal matrix and implant-based reconstruction. Issue 6 (June 2021) - Aliotta, Rachel E.; Duraes, Eliana F.R.; Scomacao, Isis; Morisada, Megan; Orra, Susan; Moreira, Andrea; Bernard, Steven; Schwarz, Graham; Djohan, Risal
Summary: Introduction: The use of acellular dermal matrix (ADM) for breast reconstruction continues to change in both single- and two-stage reconstruction. Determining optimal outcomes clinically, aesthetically, financially as well as for the patient's quality of life has become a priority. Methods: A retrospective review of implant-based reconstructions was performed at a single center from 2010 to 2016, with patients blindly matched 1:1:1 into three cohorts based on reconstruction type: 1) single stage direct to implant with ADM, 2) two-stage tissue expander to implant (TE/I) without ADM, and 3) two-stage TE/I with ADM. Relative cost between groups, esthetic outcomes, and quality of life within each group was analyzed. Results: Group 1 was more likely to be older and use intraoperative angiography, but with fewer overall surgeries and postoperative visits ( p <0.001). There was no statistically significant difference in reconstructive success among all three groups ( p  = 0.85). Cost was significantly higher for group 3 relative to groups 1 and 2. Overall appearance was higher in groups 1 and 3 relative to group 2, with radiation therapy the only independent factor. Group 1 had higher scores using Breast-Q for the physical well-being domain ( p  = 0.01). Conclusion: This is the first study to incorporate clinical outcomes, esthetic visual grading, and patient-reported quality within the same cohort of individuals, considering both use of ADM and staging. Despite the added ADM cost, it is proven safe, eliminates time and cost associated with tissue expanders, decreases post-operative visits and can lead to equally as functional and aesthetically pleasing outcomes in single- and two-stage breast reconstructions.